Dinamika Perkembangan Kepribadian Remaja Remaja dalam Lingkungan Keluarga Toxic - Ilhami Latifah; Sri Nurhayati Selian (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to understand the impact of toxic family environments on individuals’ mental health, social functioning, and personality development using a descriptive qualitative approach. Data were collected through in-depth interviews and observations of three participants who had experienced non-harmonious family conditions, and were analyzed thematically. The findings indicate that toxic families are characterized by unhealthy communication, imbalanced parenting styles, and a lack of emotional support, which lead to anxiety, low self-esteem, difficulties in emotion regulation, and challenges in social relationships. These effects also persist in the long term, influencing individuals’ thought patterns and interpersonal relationships. However, individuals can cope with these conditions through coping strategies, self-awareness, and support from external environments; therefore, it is important to create healthier family environments to support individuals’ psychological well-being.